Park Street looking towards Beacon Street, ca. 1860-90 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northwest of Park Street looking towards Beacon Street. The dome and facade of the Massachusetts State House, which is located on Beacon Street, is visible along the center-right side of the carte-de-visite. The Boston Common, which is separated from the southwest side of Park Street by a wrought-iron fence, is included in left-half of the photograph. Houses and street-lights line the northeast side of Park Street. A horse-drawn carriage is located on Park Street near the intersection with Beacon Street. 4 7/16 x 7 Photographs